ANALISIS PENERAPAN AKUNTANSI PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN KOLAKA TIMUR - Kirana, Elsa; Chairunnas, Arnadi; Pracita, Sri Ayu; Bustang, Bustang (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the implementation of Article 21 Income Tax (PPh 21) accounting on employee salaries at the Regional Office of National Unity and Politics of East Kolaka Regency and to identify the factors causing differences in tax calculations compared to the applicable regulations, particularly Law Number 7 of 2021 concerning the Harmonization of Tax Regulations. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation, and analyzed by comparing the institution’s tax calculations with prevailing tax regulations. The results indicate that, in general, the implementation of PPh 21 has followed established procedures; however, discrepancies in tax calculations still occur due to inaccuracies in determining employees’ Non-Taxable Income (PTKP) status, resulting in higher tax liabilities than should be imposed. Therefore, periodic updates of employee administrative data are necessary. Keywords: Tax Accounting, Article 21 Income Tax, Non-Taxable Income (PTKP), Government Institution